MENENTUKAN DOSIS SILASE JEROAN IKAN HIU (Rhizoprionodon sp.) DALAM FORMULA PAKAN IKAN LELE DUMBO (Clarias gariepinus) - Ramli Ramli (Faculty of Science and Technology University Ibrahimy, 2015)
Increased commercial feed African catfish (Clarias gariepinus) are not dimbangi with an increase in sales price of production, so as necessary to find a cheap alternative feed and nutrients according to the needs of African catfish. Offal shark (Rhizoprionodon sp.) Can be used as alternative feed with fermented silage first being to improve the quality of its nutritional value. This study aims to determine the effect and dose utilization of sharks in offal silage feed formula to the growth of African catfish (Clarias gariepinus.). The experimental design used was completely randomized design (CRD) with 5 treatments and 3 replications that substitution treatment offal silage protein sharks against fish meal protein. The results showed the best dose offal silage sharks to substitute protein fish meal in fish feed formulas African catfish is amounted at 63.50% for the specific growth rate of 5.004% of body weight / day; 63.50% for feed conversion ratio of 1.21; 41.67% for protein efficiency ratio 0.049; 57.93% to 25.40% protein retention and 52.00% for the activity of the protease enzyme tyrosine 12.31 mol / g.menit.